Nakam: The Holocaust Survivors Who Sought Full-Scale Revenge. Dina Porat - Dinkelaker, Philipp (Holocaust and genocide studies, 2024)
Jewish vengeance is not a new topic. In fact, the myth of "Jewish vindictiveness" was a key item within Nazi antisemitism. Hitler often misrepresented the